2006
DOI: 10.1364/oe.14.002921
|View full text |Cite
|
Sign up to set email alerts
|

Resonant-plasmon field enhancement from asymmetrically illuminated conical metallic-probe tips

Abstract: Optical-field enhancement and confinement for an asymmetrically illuminated nanoscopic Au tip suspended over a planar Au substrate is investigated both numerically and experimentally. The spatial field distribution of the tip-sample system was calculated using the full 3D finite-difference time-domain method. The calculation enables investigation of the effects of the substrate-tip placement, angle of incidence, and spectral response. The tip plasmon response leads to a significant (up to ~70 times) local fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
97
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(105 citation statements)
references
References 37 publications
(49 reference statements)
7
97
1
Order By: Relevance
“…However, care must be taken when simulating geometries with abrupt curvature and high field gradients. Detailed investigations of the field enhancement offered by different probe tips have been conducted using the multiple multipole, 112,113 finite element time domain, 114 finite difference time domain, 101,115 and finite element 108 techniques. The field enhancement at the apex of sharp probe tips has allowed for apertureless SNOM fluorescence imaging 116 down to single molecules.…”
Section: B Near-field Of a Sharp Probementioning
confidence: 99%
“…However, care must be taken when simulating geometries with abrupt curvature and high field gradients. Detailed investigations of the field enhancement offered by different probe tips have been conducted using the multiple multipole, 112,113 finite element time domain, 114 finite difference time domain, 101,115 and finite element 108 techniques. The field enhancement at the apex of sharp probe tips has allowed for apertureless SNOM fluorescence imaging 116 down to single molecules.…”
Section: B Near-field Of a Sharp Probementioning
confidence: 99%
“…The extraordinary sensitivity of tip-enhanced Raman scattering spectroscopy has been demonstrated for resonant [1][2][3][4] as well as non-resonant molecules. [1,5] The method has the potential to reach single-molecule sensitivity, as recently shown for molecules that are resonant at the excitation frequency.…”
Section: Introductionmentioning
confidence: 99%
“…[1,5] The method has the potential to reach single-molecule sensitivity, as recently shown for molecules that are resonant at the excitation frequency. [3,6,7] However, tip-enhanced optical microscopy has so far been restricted to transparent [8,9] and semitransparent [1,2,10] samples with tip illumination from below. The first experimental demonstrations of tip-enhanced Raman spectroscopy (TERS) used rough silver films on transparent microscope slides supporting the molecules of interest.…”
Section: Introductionmentioning
confidence: 99%
“…asymmetric plasmonic nanoparticles have been studied by many world class researchers; Ryan et al, [15] have reported field enhancement induced between a metallic tip and metallic substrate [15]. The enhancement of the field has been investigated in multi-material trimmer nanostructures composed of Au nanoparticles surrounded by two Ag nanoparticles as a function of the gap between the two Ag nanoparticle and their size.…”
mentioning
confidence: 99%
“…The diffraction and interference of the out coupled waves are investigated by using, in-house, the 3D-Finite Difference Time Domain (3D -FDTD) technique [17], [18]. The FDTD grid is excited using the total-field/scattered field formulation [15] with plane-wave polarized parallel to the x-axis. The source is placed at the cell grid number 4 after the PMLs.…”
mentioning
confidence: 99%